RETRACTED: Influence of Resources on Cue Preferences in Mate Selection - Hou, Juan; Shu, Tianxin; Fang, Xiaoyi (Frontiers in Psychology, 2020)
According to the research on the influence of resources on mate selection, the amount of financial resources affects an individual’s choice of "luxuries" and "necessities" among mate selection cues, while the amount of time resources affects cue diversity. However, for a long time, researchers only paid attention to the impact of financial resources and ignored the role of time resources. Therefore, this paper draws lessons from the relevant research on the influence of time on decision-making and proposes to study mate selection from the perspective of decision-making. Additionally, current research concerning the influence of resources on the choice of a spouse focuses more on results and neglects to examine the process. Therefore, based on the relevant theories, this paper makes several theoretical assumptions regarding the influence mechanism of resource availability on mate choice decisions, gender differences and the actor-partner effect.